Evaluation of the Enzymatic Activity of Soluble CD13/APN and CD26/DPP4 in Serum and Urine Samples of Mice with Experimental Autoimmune Encephalomyelitis - Mami, Sanaz; Farahani, Elnaz; Sotoodehnejadnematalahi, Fattah; Fathollahi, Anwar; Hajimolahoseini, Mostafa; Pouriran, Ramin; Yeganeh, Farshid (Novelty in Biomedicine, 2021)
Background: Dipeptidyl Peptidase IV (DPP4/CD26) and Amino Peptidase N (APN/CD13) have essential roles in inflammatory diseases. The current study aimed to determine changes in APN and DPP4 enzyme activity in the serum and urine of mice with experimental autoimmune encephalomyelitis (EAE). Materials and Methods: In the present study, female C57BL/6 mice were studied in two groups (control and EAE). Twenty-sevendays after induction, the enzymatic activity of APN and DPP4 in urine and serum samples was measured using a spectrophotometric assay. Results: The enzyme activity of DPP4 was higher in serum and urine of EAE mice than in the control group (mean in serum: 1.04 ± 0.13 pmol/mL and 0.80 ± 0.12 pmol/mL, respectively, P=0.015; mean in urine: 0.26 ± 0.04 pmol/mL and 0.19 ± 0.04 pmol/mL, respectively, P=0.015). However, the enzymatic activity of APN in serum and urine of mice with EAE when compared to the control group had no significant difference (mean in serum: 9.20 ± 1.15 unit/mL and 10.25 ± 1.21 unit/mL, respectively, P=0.132, mean in urine: 0.23 ± 0.27 unit/mL and 0.15 ± 0.05 unit/mL, respectively, P=0.310). Conclusion: The increased DPP4 activity along with normal APN activity in urine and serum samples can be used as an indicator to detect or follow up on the course of MS disease. Confirmation of this finding needs further investigation.